2015
DOI: 10.1016/j.resuscitation.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Targeted temperature management and neuroprognostication after cardiac arrest: A survey in Belgium

Abstract: The prognosis of patients who are admitted to the hospital after cardiac arrest often relies on neurological examination, which could be significantly influenced by the use of sedative drugs or the implementation of targeted temperature management. The need for early and accurate prognostication is crucial as up to 15-20% of patients could be considered as having a poor outcome and may undergo withdrawal of life-sustaining therapies while a complete neurological recovery is still possible. As current practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
2
3
0
Order By: Relevance
“…Besides controversies concerning the best temperature to be achieved in comatose survivors after CA, there is still a tendency in Brazil to induce hypothermia for those patients, despite the rhythm. These results are in line with the clinical practice demonstrated in Belgium, by Taccone et al [3]. Another survey performed in France, with more than 3000 doctors showed very similar results − about 56% of doctors still induce hypothermia (32-34 • ) in comatose patients after CA.…”
supporting
confidence: 87%
“…Besides controversies concerning the best temperature to be achieved in comatose survivors after CA, there is still a tendency in Brazil to induce hypothermia for those patients, despite the rhythm. These results are in line with the clinical practice demonstrated in Belgium, by Taccone et al [3]. Another survey performed in France, with more than 3000 doctors showed very similar results − about 56% of doctors still induce hypothermia (32-34 • ) in comatose patients after CA.…”
supporting
confidence: 87%
“…This survey showed a high rate of implementation of TTM and SOPs in post-resuscitation care in Italy, as also previously reported by other national surveys [4,5]. Overall, a better post-resuscitation care was observed in ICUs that admitted more than 10 CAs/year, compared to those with a smaller admission of CAs (Fig.…”
supporting
confidence: 87%
“…Only 11.4% had performed EEG in routine practice in this study. However, recent surveys reported the widely use of EEG in CA patients 19,20 . Friberg et al reported that 74% of members from European Society of Emergency Medicine had used intermittent EEG or continuous EEG for CA patients in practice 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent surveys reported the widely use of EEG in CA patients. 19,20 Friberg et al reported that 74% of members from European Society of Emergency Medicine had used intermittent EEG or continuous EEG for CA patients in practice. 20 The low level utility of EEG in China is likely due to several causes.…”
Section: Discussionmentioning
confidence: 99%